2019
DOI: 10.1111/epi.14663
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor network hypersynchrony as an endophenotype in families with genetic generalized epilepsy: A resting‐state functional magnetic resonance imaging study

Abstract: Summary Recent evidence suggests that three specific brain networks show state‐dependent levels of synchronization before, during, and after episodes of generalized spike‐wave discharges (GSW) in patients with genetic generalized epilepsy (GGE). Here, we investigate whether synchronization in these networks differs between patients with GGE (n = 13), their unaffected first‐degree relatives (n = 17), and healthy controls (n = 18). All subjects underwent two 10‐minute simultaneous electroencephalographic–functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
(42 reference statements)
2
11
0
Order By: Relevance
“…Hyperactivations in motor systems have been suggested as endophenotypes of JME during cognitive fMRI, 13 , 14 but also for a mixed GGE cohort during resting-state. 30 We complement these findings by studying much faster neuronal oscillations using MEG and without vascular confounds. Our results point to more globally increased network levels in patients with GGE and siblings, irrespective of a task involved.…”
Section: Discussionmentioning
confidence: 81%
“…Hyperactivations in motor systems have been suggested as endophenotypes of JME during cognitive fMRI, 13 , 14 but also for a mixed GGE cohort during resting-state. 30 We complement these findings by studying much faster neuronal oscillations using MEG and without vascular confounds. Our results point to more globally increased network levels in patients with GGE and siblings, irrespective of a task involved.…”
Section: Discussionmentioning
confidence: 81%
“…Sensorimotor network was well-studied in epilepsy patients. Rolandic epilepsy is a form of well-characterized childhood epilepsy whose focal electroencephalographic abnormalities affect the same well-delineated local brain regions, rs-fMRI study found that the patients with Rolandic epilepsy exhibited less connectivity among the sensorimotor areas ( 29 ); another rs-fMRI study found that the synchrony was significantly higher in the sensorimotor network in IGE patients and in their unaffected relatives when compared to controls, also there was a trend toward higher synchrony in the generalized spike-wave discharges (GSW) network in patients and their unaffected relatives, those findings provide evidence that elevated fMRI BOLD synchrony in a sensorimotor network may be a state-independent endophenotype of IGE, present in patients in the absence of GSW, and present in unaffected relatives ( 30 ). In current study, the Frequency and Coverage of microstate A were larger in patients with IGE with seizures in the previous 2 years than in those without such seizures and in HCs, indicates that the sensorimotor network was altered in IGE patients and provide new evidence to support the previous rs-fMRI study ( 30 ).…”
Section: Discussionmentioning
confidence: 87%
“…These regions also displayed increased geodesic distance, suggesting network isolation and decreased efficiency (Wandschneider et al, 2019 ). Similarly, in GGE populations, elevated sensorimotor network synchrony (Tangwiriyasakul et al, 2019 ) and interictal cortical power and connectivity (Stier et al, 2021 ) have been reported in patients and their asymptomatic siblings. These subtle but similar patterns in asymptomatic siblings suggest that genetic mechanisms might play a role in the abnormal development of thalamofrontal brain networks.…”
Section: Imaging Endophenotype In Common Epilepsymentioning
confidence: 88%